Peran Praktisi Dalam Pengembangan Teori dan Proses Pembelajaran Untuk Sekolah Bisnis - Jony Oktavian Haryanto (Jurnal Administrasi Bisnis, 2009)
The decreasing number of intakes and quality of the students, and crisis identityhave jeopardise the survival of business schools. There must be a breakthrough toovercome these hard situation. One of the solution is theories-in-use approach, whichis needed to develop the appropriate theory. The writer also suggests to recruit practitionersas the faculty members. This will encourage original theories developmentwhich is appropriate for third world countries like Indonesia. The other solutionis to send the existing lecturers to join the consulting and encourage them to havethe knowledge of practice world. By doing these, hopefully better condition will beachieved.Keywords: theories-in use, general theory, original theories development